Sumber Belajar Biologi Berupa Majalah Pada Materi Jamur Untuk Siswa Sekolah Menengah Atas - Alfin ipin (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2018)
The objectives of this study is to develop learning resources in the form of Biology magazines on mushroom material for sudents of senior high school 3 Muara Bungo with valid categories. The type of this Research is Research and Devlopment. The model of Development used was four-D model which consists of define, design, and development. In the define stage conducted curriculum analysis , student analysis, task analysis, concept analysis. Design stage conducted by designing Biology magazine. Furthermore, in the development stage conducted expert validation, test of ten grade students MIA I and MIA II at senior high school 3 Muara Bungo. The research data of feasibility test was obtained by questionnaire of student’s response. The results of this study was questionnaire responses of then grade students MIA I and MIA II and has beech declared eligible with the pncentage of students who stated strongly agree with the magazine developed were 3,43%, students who agree were 7,84%, students who disagree were 0,5%, and students who strongly disagree were 0,21% based on theresults conducted it can be concluded Biology magazine on mushroom material for senior high school studnts were elegible to use.Keywords: Magazine, Mushroom, Four-D, Student